Combination of Betulinic Acid Fragments and Carbonic Anhydrase Inhibitors-A New Drug Targeting Approach - Matthias Bache; Niels V. Heise; Andreas Thiel; Anne Funtan; Franziska Seifert; Marina Petrenko; Antje Güttler; Sarah Brandt; Thomas Mueller; Dirk Vordermark; Iris Thondorf; René Csuk; et al. (MDPI AG, 2024)
Human carbonic anhydrase IX (hCA IX) is a zinc(II)-dependent metalloenzyme that plays a critical role in the conversion of carbon dioxide and water to protons and bicarbonate. It is a membrane-bound protein with an extracellular catalytic center that is predominantly overexpressed in solid hypoxic tumors. Sulfamates and sulfonamides, for example acetazolamide (AZA), have been used to inhibit hCA IX in order to improve the response to solid hypoxic tumors. In the present study, we propose a new drug targeting approach by attaching the natural cytotoxic substances betulin and betulinic acid (BA) via a linker to sulfonamides. The conjugate was designed with different spacer lengths to accumulate at the target site of hCA IX. Computational and cell biological studies suggest that the length of the linker may influence hCA IX inhibition. Cytotoxicity tests of the newly synthesized bifunctional conjugates 3, 5, and 9 show effective cytotoxicity in the range of 6.4 and 30.1 µM in 2D and 3D tumor models. The hCA IX inhibition constants of this conjugates, measured using an in vitro enzyme assay with p-nitrophenyl acetate, were determined in a low µM-range, and all compounds reveal a significant inhibition of hypoxia-induced CA activity in a cell-based assay using the Wilbur-Anderson method. In addition, the cells respond with G1 increase and apoptosis induction. Overall, the dual strategy to produce cytotoxic tumor therapeutics that inhibit tumor-associated hCA IX was successfully implemented.